1995
DOI: 10.1039/c39950000055
|View full text |Cite
|
Sign up to set email alerts
|

The third-order optical non-linearity of the phenylethynyl-substituted benzene system

Abstract: Phenylethynyl siJbstituted benzenes 1, 2 and 3 are synthesized by the Pd-coupling reaction of phenylacetylene with the corresponding bromobenzene; the third-order optical non-linearity [X(3)(03)1 increases with the participation of n-conjugation through the triple bond as determined by the degenerate four-wave mixing (DFWM) method in a c h I o rof o rm sol u:i on.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 3 publications
2
63
0
Order By: Relevance
“…169°C was characterized by 1 H NMR (270 MHz) and IR spectroscopy and again claimed as hexatolane 1. [7] The authors also provided a UV/Vis spectrum of this product, which appears similar but not identical to that published in 1987 by Praefcke. [6,24] In the course of our studies, [1] we performed the Pd 0 -catalysed phenyethynylation of hexahalobenzenes 3 and 4 under the different previously described conditions.…”
Section: Introductionmentioning
confidence: 79%
“…169°C was characterized by 1 H NMR (270 MHz) and IR spectroscopy and again claimed as hexatolane 1. [7] The authors also provided a UV/Vis spectrum of this product, which appears similar but not identical to that published in 1987 by Praefcke. [6,24] In the course of our studies, [1] we performed the Pd 0 -catalysed phenyethynylation of hexahalobenzenes 3 and 4 under the different previously described conditions.…”
Section: Introductionmentioning
confidence: 79%
“…[25][26][27][28][29] Subsequent studies suggest that these materials have attractive electronic properties. [29][30][31][32][33][34][35] L. D. Pan et al reported that graphyne nanoribbons are semiconductors with band gaps similar to silicon.…”
mentioning
confidence: 99%
“…Spectroscopic work 41 suggests that a dendrimer-like aggregate with 6-fold symmetry does not exhibit the desired exciton localization, since it is lost through ortho and parasubstitution across a phenyl linkage. The meta substitution of the BA 3 aggregate acts to separate the dendrimeric chain of which it is part into regions with a distinct electronic integrity.…”
Section: Discussion: Structure and Mechanismsmentioning
confidence: 99%